2015
DOI: 10.1016/j.fuproc.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of product selectivity in the conversion of ethanol to hydrocarbons over H-ZSM-5 based zeolite catalysts

Abstract: Conversion of ethanol to hydrocarbons was investigated over H-ZSM-5 zeolite and its modification by addition of phosphorus, iron and nickel. Reaction is realized in a tubular flow reactor at atmospheric pressure. Catalyst characterization was performed by UV-vis, TG-DTA, XRD, NH3-TPD, and IR spectroscopy of the surface OH groups and of adsorbed pyridine. High P content enhances the selectivity to lower olefins, in particular ethylene, as also occurs in the case of Fe addition. Over Ni-modified zeolites, C4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 41 publications
2
28
0
3
Order By: Relevance
“…2). Esse resultado também foi observado em [14]. Analisando-se as temperaturas desses picos de dessorção, observou-se que para o catalisador que contém 2,5% de Ni, ocorreu deslocamento dos mesmos para temperaturas mais baixas, indicando que a acidez dos sítios ativos foi levemente diminuída [22].…”
Section: Caracterização Dos Catalisadoresunclassified
See 1 more Smart Citation
“…2). Esse resultado também foi observado em [14]. Analisando-se as temperaturas desses picos de dessorção, observou-se que para o catalisador que contém 2,5% de Ni, ocorreu deslocamento dos mesmos para temperaturas mais baixas, indicando que a acidez dos sítios ativos foi levemente diminuída [22].…”
Section: Caracterização Dos Catalisadoresunclassified
“…Uma variedade de produtos foi detectada, incluindo olefinas leves, parafinas leves, aromáticos e uma fração pesada consistindo de hidrocarbonetos C 5+ que são formados via conversão consecutiva do etileno. Phung et al [14] estudaram a seletividade para os produtos na conversão do etanol, utilizando como catalisadores a zeólita HZSM-5 modificada com P, Fe e Ni, em diferentes teores. …”
unclassified
“…Commonly, when the reaction is carried out at 150 -300 °C, diethyl ether is the main product. At higher temperature, ethylene selectivity increases, but it decays at temperature higher than 400 -500°C due to formation of higher hydrocarbons and aromatics [2,[16][17][18][19]. Many byproducts are reported, such as acetic acid, ethyl acetate, A c c e p t e d M a n u s c r i p t 7 acetaldehyde, acetone, methanol, methane, propane, propylene, butane, butenes, hydrocarbons, carbon dioxide, carbon monoxide and hydrogen, besides possible coke formation by surface polymerisation of ethylene.…”
mentioning
confidence: 99%
“…The choice to add a metal phase is based on previous studies on products distribution at variable temperature. Increasing the operating temperature, together with water addition may improve catalyst life, although Phung et al [18] observed decreasing ethylene selectivity at increasing temperature due to the formation of higher alkanes and olefins. Ni was therefore chosen as co-catalyst due to large availability, low cost with respect to noble metal competitors and high activity for the decomposition of the expected byproducts.…”
mentioning
confidence: 99%
“…Many research commonly studied the use of pure ethanol as a feedstock for ethanol dehydration and few research have been investigated on the dehydration of a mixture of water and pure ethanol [8], [10]- [14]. The use of a low purity of ethanol produced by simple flash distillation or a crude bioethanol limiting the purification processes may result in a lower production cost of ethanol dehydration compared to that of a pure ethanol.…”
mentioning
confidence: 99%